2016
DOI: 10.1016/j.ribaf.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Stock markets’ bubbles burst and volatility spillovers in agricultural commodity markets

Abstract: Our paper focuses on commodity financialization and the gradual integration between commodity and financial markets, investigating to what extent shocks in stock markets impact commodity price volatility, and the persistency of the phenomenon. To this end, we estimate Volatility Impulse Response Function from stock markets to agricultural commodity markets over a symmetric window before and after two of the most important bubble bursts since the new millennium, the 2000 dot.com bubble and the 2008 financial cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The authors conclude that, after 2006, risk transmission emerged as another dimension of the dynamic interrelationships between energy and agricultural markets. Furthermore, Baldi et al found that volatility spillover from financial markets to agricultural commodity markets increased significantly after the 2008 financial crises . Similarly, Nazlioglu et al found no volatility spillover between oil and agricultural commodity markets before the so‐called food price crisis around 2006 but, on the other hand, they found that oil volatility transmitted to the wheat, corn, and soybean markets after the crisis .…”
Section: Theoretical Framework Of Underlying Mechanismsmentioning
confidence: 99%
“…The authors conclude that, after 2006, risk transmission emerged as another dimension of the dynamic interrelationships between energy and agricultural markets. Furthermore, Baldi et al found that volatility spillover from financial markets to agricultural commodity markets increased significantly after the 2008 financial crises . Similarly, Nazlioglu et al found no volatility spillover between oil and agricultural commodity markets before the so‐called food price crisis around 2006 but, on the other hand, they found that oil volatility transmitted to the wheat, corn, and soybean markets after the crisis .…”
Section: Theoretical Framework Of Underlying Mechanismsmentioning
confidence: 99%
“…Among the main causes, some authors indicate the strong increase in the demand for food commodities from China and India and the uncontrolled increase in oil price, which has had repercussions throughout the economy and in particular on the fertiliser market and the transport one [26][27][28]. Others stress the role of financial speculation [28][29][30][31], which caused considerable price volatility and prevented the planning of supply in many countries while contributing to create a situation of marked instability. Moreover, the rush to biofuels still remains a commonly considered factor in relation to the increasing quantities of agricultural products that are being diverted away from their traditional food markets, even if also on this aspect the literature is not unanimous [17,28,29,[32][33][34].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Also wine indexes have emerged to cater for fine wine demand from investors. They can be both independent, as the ones reported by Liv-Ex website, or constructed by a financial institution as Monte dei Paschi di Siena with its "MPS Wine Index" 6 .…”
Section: Frameworkmentioning
confidence: 99%
“…Existing literature has so far focused on the financialization of several types of commodities, such as grain, corn, soybeans, cotton, tobacco, water (Sanning et al, 2007;Masset and Henderson, 2008 1 For recent evidences on commodity "financialization" see Baldi et al, 2016. Wine is a commodity of growing importance in the so-called "Old World" countries, such as Italy and France that historically dominated the market, as well as in "New World" countries, like Australia and the United States that more recently have displayed relevant rates of increase. Despite these recent market trends, wine as a financial alternative asset class has been understudied.…”
Section: Introductionmentioning
confidence: 99%